2018
DOI: 10.1111/vsu.12795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐level laser therapy on the healing of surgically closed incisions and surgically created open wounds in dogs

Abstract: Results of this study do not support recommending LLLT to stimulate healing of uncomplicated, small wounds and incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
(48 reference statements)
2
16
1
Order By: Relevance
“…Such studies have confirmed the correlation between histologic characteristics of wound healing with visual assessment of clinical scar outcome. The information extrapolated from this study, and the Gammel et al (23) study, proves that it is achievable to establish a reliable clinical scar scale using digital photography (23). This high level of correlation therefore indicates that this is a viable method to use when analyzing surgically created wounds treated with ancillary therapy such as PBM induced by laser therapy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Such studies have confirmed the correlation between histologic characteristics of wound healing with visual assessment of clinical scar outcome. The information extrapolated from this study, and the Gammel et al (23) study, proves that it is achievable to establish a reliable clinical scar scale using digital photography (23). This high level of correlation therefore indicates that this is a viable method to use when analyzing surgically created wounds treated with ancillary therapy such as PBM induced by laser therapy.…”
Section: Discussionsupporting
confidence: 58%
“…The use of digital photography as a valid means to evaluate the efficacy of wound healing using specific treatment modalities is of particular value because it allows for gross patient evaluation and does not necessitate histologic confirmation (3, 21). This method of evaluation has been more specifically explored using porcine burn scars, human skin grafts and a more recent canine laser study (18, 23, 24). Such studies have confirmed the correlation between histologic characteristics of wound healing with visual assessment of clinical scar outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Gammel et al . [ 14 ] reported that irradiation of 980 nm LILT with fluence of 5 J/cm 2 once a day for 5 days did not enhance wound healing of small incisions and uncomplicated wounds in dogs. Recently, in a study by Kennedy et al .…”
Section: Introductionmentioning
confidence: 99%
“…The case report by Lucroy et al (1999) added very little to the weight of evidence and was especially hard to compare to the others as it looked at a chronic wound as opposed to acute wounds. The papers which contributed the most to strengthening the evidence available were by De Braekt et al (1991), Kurach et al (2015), and Gammel et al (2018). All three papers had a good randomised control study design with objective as well as subjective assessment of standardised wounds.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%